MOEL: Wachstumsvorsprung gegenüber Westeuropa bleibt erhalten; CEEC Growth Still Overtakes Western Europe - Vasily Astrov (The Vienna Institute for International Economic Studies (wiiw), 2008)
Die MOEL verzeichneten 2007 erneut ein kräftiges Wirtschaftswachstum. In den neuen EU-Ländern in Mitteleuropa, deren Expansion primär durch die Re-Industrialisierung geprägt ist, war ein Anstieg der Beschäftigung zu beobachten. In den anderen MOEL wurde die Entwicklung jedoch vor allem vom Dienstleistungssektor getragen und basierte nach wie vor teilweise auf der Ausweitung der Kreditvergabe der Banken, die allerdings in mehreren Ländern etwas gebremst wurde. Die Folgen der weltweiten Finanzmarktturbulenzen und eine Wachstumsverlangsamung in Westeuropa dürften die Konjunkturaussichten der MOEL nur unwesentlich dämpfen; der latente Arbeitskräftemangel und anhaltender Inflationsdruck aufgrund der Verteuerung von Energie und Agrarprodukten auf dem Weltmarkt könnten sich jedoch mittelfristig als Wachstumshemmnis erweisen. – – Economic growth in Central and East European countries (CEECs) in 2007 was driven primarily by strong domestic demand, especially for consumer goods. The latter resulted from both higher incomes (particularly in Central Europe's new EU countries) and expanding household credit (elsewhere), although the pace of credit expansion has slowed down somewhat, not least due to government efforts to avoid excessive 'overheating'. Another distinction between these two country groups has been in the sectoral patterns of growth the main growth engine was industry in the Central European new EU countries and the services sector elsewhere. The higher world prices for food and energy and further tightening of domestic labour markets led to mounting inflationary pressures. The latter proved to be particularly strong in the poorer CEECs, but was mitigated by an ongoing currency appreciation in Poland, Slovakia and the Czech Republic. The recent surge in inflation is unwelcome news for the new EU countries aiming to join the European Monetary Union soon (especially the Baltic states, but in the longer term also Bulgaria and Romania); only Slovakia has a realistic chance to join the euro zone already at the beginning of 2009 as aspired to by the country's government. At the same time, higher inflation and further budget consolidation have improved the fiscal performance of several new EU countries; the latter is no longer a formal obstacle to adopting the euro (with the exception of Hungary). In contrast, fiscal policy in Russia and Ukraine has been somewhat loosened. Russia's sovereign oil fund, which has been booming recently thanks to soaring world crude prices, is being increasingly spent on industrial policy, aimed at diversifying the country's economic structure away from energy. The current turbulence in the global financial markets and a slowdown in Western Europe should dampen the CEECs' growth prospects in 2008 only marginally. The speed of their real convergence to the EU 15 will most probably stay at around 3.5 percentage points on average. Hungary's economic growth should even pick up slightly, as consumer demand will gradually recover from the adverse effects of last year's budget consolidation. At the same time, in Latvia and Estonia, 'hard landing' following a protracted period of demand overheating appears inevitable. The prospects of EU accession for a number of Southeast European countries have recently improved and should contribute to the region's overall stability and economic development. However, Serbia might suffer from the recent 'Kosovo crisis' and the potentially destabilizing consequences of the recent fiscal loosening ahead of the parliamentary elections in May 2008, whereas Turkey remains vulnerable to fluctuations in the world financial markets.
Additional information: Sonderdruck aus: Monatsberichte des Österreichischen Instituts für Wirtschaftsforschung - WIFO, 81. Jahrgang, Heft 5, 2008
Keywords: P2; O57; E17; O4; 330; transitional economies; comparative study; economic growth; fiscal and monetary policy; macroeconomic forecast; macroeconomic analysis